Mexametric Assessment of Melanin Level in Children's Skin - V. A. Shamrikova; E. D. Sorokina; E. V. Dubrovskaya; Y. A. Krakhaleva; E. A. Kurniavkina; Y. M. Krinitsyna; A. I. Yakubovich; I. G. Sergeeva (Acta Biomedica Scientifica)
Background. High predisposition to sunburn in childhood and associated increased risk of malignant skin tumors development, decrease with age. There is a likelihood of a relationship between the described trends and dynamic age related changes in functional state of melanocytes and melanin.Aim: to evaluate the level of melanin in the skin in children of different age. Materials and methods. The study involved 78 children aged from 7 to 17 years, without any disorders of skin pigmentation. Three groups of observations were formed: Group 1 - 28 children from 7 to 9 years, Group 2 - 25 children from 10 to 12 years, Group 3 - 25 children from 16 to 17years. The melanin level was evaluated in the skin of face, body and extremities using mexametry.Results. The highest level of skin melanin was observed in forearms and lower legs in all age groups (up to 28.3 ± 10.8, 23.3 ± 8.6 and 26.7 ± 10.6 c.u. in Group 1, 2 and 3 respectively), the lowest - in cheeks and chest (up to 8.0 ± 4.7, 4.4 ± 3.4 and 9.5 ± 4.1 c.u. in Group 1, 2 and 3 respectively). There were relationships between skin site and level of melanin, but no relationships between level of melanin and gender or age.Findings. The level of melanin in the skin in children aged from 7 to 17 years is individual and depends on the location of the skin area, but does not depend on gender or age. The distribution of melanin in the skin is stable and does not change over time.